Study on the Financial Performance of Companies Operating in the Pharmaceutical Industry in Romania (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
The study aims at determining the financial performance of companies in the pharmaceutical industry between 2009 and 2014 by means of the indicator of the financial return rate, using multiple linear regressions as research method. By analysing the evolution of the share of companies in the pharmaceutical industry based on the trend of the financial rate of return, we can estimate that the number of entities that resort to supporting the financial activities from loans and liabilities is growing in the period under analysis. This is due mainly to the liquidity crisis faced by entities, as a result of the high recovery duration of debts. Also, using the multiple linear regression we can highlight that, the financial return of pharmaceutical companies is positively influenced by their economic profitability, by the equity multiplier and by inflation, and negatively, by the net profit margin.